2008
DOI: 10.1021/ef800338j
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Biodiesel from Palm Kernel Oil on the Engine Performance, Exhaust Emissions, and Combustion Characteristics of a Direct Injection Diesel Engine

Abstract: Palm kernel oil is extracted from palm fruit as well as palm oil and is considered to be a potential feedstock for biodiesel production. The objective of this paper is to evaluate the feasibility of using biodiesel from palm kernel oil on a direct injection (DI) diesel engine under three different engine speeds and at various gradational engine load conditions. Experimental results demonstrate that the brake specific fuel consumption (BSFC) increased as the percentage of palm kernel oil methyl ester (PKOME) fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…When the engine speed was increased above 1300 rpm, the RSO biodiesel NO x tended to reduce until 2000 rpm was reached. It is noted that higher NO x emissions at lowengine speeds have been found in previous studies where test were carried out at constant load and various engine speed conditions (Lin and Lin, 2006;Altiparmak et al, 2007;Lin et al, 2008;Lin and Li, 2009). This is probably also due to the start of 162 Combustion efficiency and performance of RSO biodiesel as alternative fuel in a single cylinder CI engine combustion being too far advanced as a consequence of being derived from its physical properties (viscosity, density, compressibility, sound velocity) as discussed before (Carraretto et al, 2004;Lapuerta et al, 2008a;Lapuerta et al, 2008b).…”
Section: Results and Discusionmentioning
confidence: 82%
“…When the engine speed was increased above 1300 rpm, the RSO biodiesel NO x tended to reduce until 2000 rpm was reached. It is noted that higher NO x emissions at lowengine speeds have been found in previous studies where test were carried out at constant load and various engine speed conditions (Lin and Lin, 2006;Altiparmak et al, 2007;Lin et al, 2008;Lin and Li, 2009). This is probably also due to the start of 162 Combustion efficiency and performance of RSO biodiesel as alternative fuel in a single cylinder CI engine combustion being too far advanced as a consequence of being derived from its physical properties (viscosity, density, compressibility, sound velocity) as discussed before (Carraretto et al, 2004;Lapuerta et al, 2008a;Lapuerta et al, 2008b).…”
Section: Results and Discusionmentioning
confidence: 82%
“…A study conducted with high oleic acid soybean biodiesel led to lower NO x emissions relative to regular soybean biodiesel indicating that fewer polyunsaturated fatty acids contributed to the improvement . Additional studies have found that oils containing less polyunsaturated fatty acids, such as palm or coconut oil, have lower NO x emissions than soybean biodiesel. ,,, Using neat methyl esters, Knothe et al determined that unsaturated fatty acids as well as those with longer chain length (>C16) can increase NO x emissions . The low prevalence of polyunsaturated fatty acids and the predominance of shorter chain length fatty acids present in C. gracilis oil (Table ) likely contribute to its low NO x emissions.…”
Section: Discussionmentioning
confidence: 99%
“…The use of vegetable oil as engine fuel is limited by its high viscosity and low volatility, which cause poor cold-start performance, misfire, and ignition delay . Transesterified vegetable oil blended up to 20% with diesel can be easily used in the existing diesel engine without any engine modification. , Thus, the present study adopted a 20% biodiesel–diesel blend.…”
Section: Introductionmentioning
confidence: 99%